Long-Term Outcomes in Uveal Melanoma After Ruthenium-106 Brachytherapy - Cennamo, Gilda; Montorio, Daniela; D’ Andrea, Luca; Farella, Antonio; Matano, Elide; Giuliano, Mario; Liuzzi, Raffaele; Breve, Maria Angelica; De Placido, Sabino; Cennamo, Giovanni (Frontiers in Oncology, 2022)
Uveal melanoma is the most common primary intraocular malignancy. The aim of this retrospective study was to report the results after 106 Ruthenium (Ru-106) plaque brachytherapy for uveal melanoma in terms of tumor control, visual acuity, radiation-related complications, tumor recur-rence, metastases and patients’ survival rate during four years follow up. A total of 355 eyes from 355 patients have been treated with Ru-106 plaque brachytherapy for uveal melanoma between February 2011 and March 2020. Five patients were lost the follow-up, then 350 eyes of 350 patients (mean age 58 ± 11 years) were enrolled in this retrospective study. All patients underwent a complete ophthalmic examination including echography, Spectral Domain-Optical Coherence Tomography. Mean follow-up was 4 years (3 months-9 years). After treatment, the mean tumor thickness was reduced to 1.75 ± 0.21 mm. Radiation complications was found in 63% of patients: 38% showed radiation maculopathy, 11% had optic neuropathy and 14% developed cataract. Cancer free survival was 99%, 97% and 85%, respectively at 5, 7 and 9 years. Ru-106 plaque brachytherapy represents a reliable treatment of uveal melanoma. This technique is valid and safe with a low rate of ocular complications during a long-term follow up.